The use of irrigation water during transition in Bulgaria's Plovdiv region - Ivan Penov (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2001)
The amount of water used for irrigation has sharply declined during transition in Bulgaria. Large sections of existing irrigation systems were abandoned, and the ones still in use are barely maintained. Crops such as wheat and barley have replaced more waterintensive crops, including vegetables, rice and maize. This problem has an impact on the future development of agriculture and the allocation of the country's water resources. The central argument is that land fragmentation in the wake of decollectivization and restitution contributes to the irrigation systems' abandonment. This paper concentrates on the institutional factors, but also considers additional factors, that may have influenced the process; further, it examines the causes driving these changes and analyses their effect on irrigation. It is based upon a review of relevant legislation, as well as field work in 17 villages located in the Plovdiv region of Bulgaria. The paper concludes that, in addition to changes in large-scale market forces and weakening of the state enforcement mechanism, institutional settings have contributed to the decline of irrigation in Bulgaria.
Keywords: 330; Bewässerung; Übergangswirtschaft; Bulgarien